Modulation of methotrexate-induced intestinal mucosal injury by dietary factors. (April 2020) - Higuchi, T; Yoshimura, M; Oka, S; Tanaka, K; Naito, T; Yuhara, S; Warabi, E; Mizuno, S; Ono, M; Takahashi, S; Tohma, S; Tsuchiya, N; et al.
Methotrexate (MTX)-induced intestinal mucosal injury in animals has been studied to understand how MTX can cause gastrointestinal disorders, but the pathogenesis of gastrointestinal disorders is still uncertain. We have attempted to reveal how dietary factors influence intestinal toxicity due to MTX. Mice were fed normal chow (NC) or a high-fat high-sucrose diet (HFHSD) before oral administration of MTX. While MTX significantly decreased the survival rates of mice fed HFHSD, the intestinal epithelial injury was detected. MTX excretion in the feces of mice fed HFHSD was reduced. Change of diets between NC and HFHSD influences the survival. The survival rates of the mice fed a high-sucrose diet or control diet were higher than those fed HFHSD. Higher survival rates were observed in mice fed a high-fat high-sucrose diet modified (HFHSD-M) in which casein was replaced by soybean-derived proteins. The survival rates of mice treated with vancomycin were lower than those administered neomycin. Microbiome and metabolome analyses on feces suggest a similarity of the intestinal environments of mice fed NC and HFHSD-M. HFHSD may modify MTX-induced toxicity in intestinal epithelia on account of an altered MTX distribution as a result of change in the intestinal environment.